General Retaliation Against The Roman Empire as Seen in William Shakespeare’s Coriolanus - Hendria, Ricky; Franchisca, Sherly (Jurnal Ilmiah Langue and Parole, 2019)
This reseacrh is titled "General Retaliation Against The Roman Empire As Seen In William Shakespeare's Coriolanus. In this research the author will discuss several issues, namely (1) How is Coriolanus's struggle in defending Rome's empire from enemy attacks? (2) What did Coriolanus do to avenge himself at the Roman empire? (3) What is the story of Coriolanus at the end of the story? the objectives of this research are (1) To analyze Coriolanus' life at the beginning of the story (2) To explain the cause of coriolanus to avenge his Roman empire (3) To study and explain how much Coriolanus's grudge to Rome to the tragic story he experienced. The theory used in this research is literary psychology theory according to Sigmund Freud. This research uses a qualitative method. The object of research is the drama Coriolanus by William Shakespeare. Data sources are divided into two, namely primary data sources and secondary data sources. The primary data source is the drama script itself. Secondary data sources are text texts and several references related to research. The data collection technique is taking notes. The technical analysis of the data is descriptive analysis. The results of the study show the following conclusions. First, the responsibility of a general in maintaining the sovereignty of his kingdom. Second, feelings of resentment arise when a struggle is not properly appreciated. Third, someone's revenge towards others can have fatal consequences and can even end in a tragic death.